Purification of serine protease from mango (Mangifera Indica Cv. Chokanan)peel using an alcohol/salt aqueous two phase system - Sarker, Md. Zaidul Islam; Amid, Mehrnoush; Shuhaimi, Mustafa; Abdul Manap, Mohd Yazid (Elsevier, 2012)
An alcohol/salt-based aqueous two-phase (ATPS) system, as a novel method of purification, was employed to purify serine proteases from mango (Mangifera Indica Cv. Chokanan) peel. The effectiveness of different parameters, such as type and concentration of alcohol (1-propanol, 2-propanol, and ethanol), type of salt (sodium citrate, potassium phosphate, and ammonium sulphate), pH, and NaCl, on the purification and selective separation of serine protease was investigated. Desirable conditions of partition coefficient (K), selectivity (S), purification factor (P), and yield (Y%) of serine protease, using ATPS, were determined. The highest partition coefficient (64.5) and selectivity (343.2) for serine protease purification value were achieved in an ATPS of 16% (w/w) 2-propanaol, 19% (w/w) potassium phosphate, and 5% (w/v) NaCl at pH 7.5. It was demonstrated that serine protease could be recovered with a yield of 96.7% and a purification factor of 11.6.